A comparative study on structural changes of LiCo1/3Ni1/3Mn1/3O2 and LiNi0.8Co0.15Al0.05O2 during first charge using in situ XRD - Yoon, Won-Sub; Chung, Kyung Yoon; McBreen, James; Yang, Xiao-Qing (ELSEVIER SCIENCE INC, 2006)
A synchrotron based in situ XRD technique was used to investigate the structural changes of Li1-xCo1/3Ni1/3Mn1/3O2 as cathode material in lithium battery during first charge in comparison with Li1-xNi0.8CO0.15Al0.05O2. The structural changes of these two cathode materials during first charge follow the similar trend as LiNiO2: an expansion along the c-axis of the unit cell with contractions along the a- and b-axis during the early stage of charge and a major contraction along the c-axis with slight expansions along the a- and b-axis near the end of charge at high voltage limit. However, the degree of disorder in Li1-xCo1/3Ni1/3Mn1/3O2 is higher than in Li1-xNi0.8Co0.15Al0.05O2, which in turn is higher than in LiNiO2. More importantly, the structural stability of Li1-xCo1/3Ni1/3Mn1/3O2 is higher than Li1-xNi0.8Co0.15Al0.05O2, which in turn is higher than LiNiO2, as reflected in the suppression of hexagonal 3 (H3) phase with collapsed c-axis formed at the end of charge. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: LITHIUM-ION BATTERIES; X-RAY-DIFFRACTION; PHASE-TRANSITIONS; CATHODE MATERIALS